1980
DOI: 10.1136/bmj.280.6216.760
|View full text |Cite
|
Sign up to set email alerts
|

Human leucocyte antigens A, B, C, and DRW in idiopathic "warm" autoimmune haemolytic anaemia.

Abstract: Summary and conclusions Twenty patients with idiopathic "warm" autoimmune haemolytic anaemia and 40 controls were typed concurrently for human leucocyte antigens (HLA) A, B, C, and DRW. There was a significantly stronger association of HLA-B8 with the disease (x2=1039; p=0018) than HLA-DRW3 (X2= 3-71; p=0 35), and the patients also showed a significant increase in BW6 homozygosity (X2=7*13; p=0-01) and a corresponding reduction in BW4 (x2=7 13; p=0 02). (All p values corrected for number of antigens at each lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Although not specifically involved in the changing landscape of AIHA, it is worth considering genetic factors and historically recognized exogenous triggers (4). Several old and recent studies demonstrated a strong association of AIHA with HLA-B locus, particularly HLA-B8 and BW6 (21), or a reduced frequency of the disease in subjects harboring the HLA-DQ6 locus (22) (Table 2). As regards humoral immune response, various variable regions of the immunoglobulin heavy and light chains (IGHV and IGKV) have been associated with AIHA, particularly IGHV4-34, IGHV3, and IGKV3-20 genes, responsible for I antigen binding, and mostly represented in CAD (6).…”
Section: Genetic Background and Exogenous Triggers For Aiha Developmentmentioning
confidence: 99%
“…Although not specifically involved in the changing landscape of AIHA, it is worth considering genetic factors and historically recognized exogenous triggers (4). Several old and recent studies demonstrated a strong association of AIHA with HLA-B locus, particularly HLA-B8 and BW6 (21), or a reduced frequency of the disease in subjects harboring the HLA-DQ6 locus (22) (Table 2). As regards humoral immune response, various variable regions of the immunoglobulin heavy and light chains (IGHV and IGKV) have been associated with AIHA, particularly IGHV4-34, IGHV3, and IGKV3-20 genes, responsible for I antigen binding, and mostly represented in CAD (6).…”
Section: Genetic Background and Exogenous Triggers For Aiha Developmentmentioning
confidence: 99%
“…The genetic background plays an important role. AIHA has been associated with HLA-B8 and BW6 locus, with a particular configuration of the variable region of the immunoglobulin heavy and light chains (IGHV and IGKV), and with polymorphism of the cytotoxic T-lymphocyte antigen-4 (CTLA-4) gene [26]. More recently, mutations of KMT2D and CARD11 genes have been reported in 69% and 31% of CAD patients [27].…”
Section: Genetic Background In Aiha Pathogenesismentioning
confidence: 99%
“…Human patients with AIHA have been reported to have increased frequencies of the HLA class I alleles, B8, (36) and B27 (37), and also reduced frequency of HLA‐DQ6 (38, 39). There are no other reports of studies on HLA class II for human AIHA, so these class I associations may reflect linkage with other MHC genes.…”
Section: Introductionmentioning
confidence: 99%